P-Selectin Sustains Extramedullary Hematopoiesis in the Gata1low Model of Myelofibrosis. (23rd October 2015) - Spangrude, Gerald J.; Lewandowski, Daniel; Martelli, Fabrizio; Marra, Manuela; Zingariello, Maria; Sancillo, Laura; Rana, Rosa Alba; Migliaccio, Anna Rita
Abstract: Splenomegaly is a major manifestation of primary myelofibrosis (PMF) contributing to clinical symptoms and hematologic abnormalities. The spleen from PMF patients contains increased numbers of hematopoietic stem cells (HSC) and megakaryocytes (MK). These MK express high levels of P-selectin (P-sel) that, by triggering neutrophil emperipolesis, may cause TGF-β release and disease progression. This hypothesis was tested by deleting the P-sel gene in the myelofibrosis mouse model carrying the hypomorphic Gata1 low mutation that induces megakaryocyte abnormalities that recapitulate those observed in PMF. P-sel null Gata1 low mice survived splenectomy and lived 3 months longer than P-sel WT Gata1 low littermates and expressed limited fibrosis and osteosclerosis in the marrow or splenomegaly. Furthermore, deletion of P-sel disrupted megakaryocyte/neutrophil interactions in spleen, reduced TGF-β content, and corrected the HSC distribution that in Gata1 low mice, as in PMF patients, is abnormally expanded in spleen. Conversely, pharmacological inhibition of TGF-β reduced P-sel expression in MK and corrected HSC distribution. Spleens, but not marrow, of Gata1 low mice contained numerous cKIT pos activated fibrocytes, probably of dendritic cell origin, whose membrane protrusions interacted with MK establishing niches hosting immature cKIT pos hematopoietic cells. These activated fibrocytes were not detected in spleens from P-sel null Gata1 low or TGF-β-inhibited Gata1 low littermates and were observed in spleen, but not in marrow, from PMF patients. Therefore, in Gata1 low mice, and possibly in PMF, abnormal P-sel expression in MK may mediate the pathological cell interactions that increase TGF-β content in MK and favor establishment of a microenvironment that supports myelofibrosis-related HSC in spleen. Abstract : There is not a single culprit. The data presented in this manuscript suggest that in the Gata1 low model, myelofibrotic stem cells are sustained in the spleen by a niche formed by the interaction of at least three distinctive cell populations. First neutrophils establish a P-selectin dependent interaction with megakaryocytes that leads to release of TGF-β. TGF-β induces the transition of a resident spleen cell population to activated fibrocytes which in turn interact with their protrusions with the megakaryocytes creating a super-cellular structure that hosts, and possibly supports, the proliferation of myelofibrotic stem cells in the spleen. See legend of Figure 7 for further details